Red Rover, Red Rover, Please Let Me Keep Rover: Pet Exemptions in Chapter 7 Bankruptcy Proceedings - Samantha Chestney (Washington University Journal of Law & Policy, 2019)
This Note identifies a gap in the Bankruptcy Code and proposes filling it. It begins by describing the Bankruptcy Code, focusing especially on the exemptions provided by the code. It then notes the limited protections these exemptions give to household pets. Given the extent to which household pets are considered a part of the family unit it considers this to be anomalous. Thus it argues the Bankruptcy Code should include an exemption for a household pet. It concludes by acknowledging the limitations to this, such as for prized breeding pets to which such a pet exemption would be inappropriate.
Keywords: Bankruptcy code; exemptions; pets